Is self-positive information more appealing than money? Individual differences in positivity bias according to depressive symptoms. Issue 8 (16th November 2016) - Takano, Keisuke; Iijima, Yudai; Sakamoto, Shinji; Raes, Filip; Tanno, Yoshihiko
ABSTRACT: The self-positivity bias, which is inherent to healthy people, is known to be blunted in depression. The lack of positive or excessive negative self-reference is considered to be a potential mechanism underlying depressive rumination. However, the motivational factors that drive people to approach and avoid emotional self-related materials are still unclear. Therefore, we measured intrinsic motivation that is associated with emotional self-references by using a reward-based decision-making task (pay-per-view paradigm). Forty-nine undergraduates completed two tasks in which they were asked to choose between negative vs. positive references (Task 1) and self vs. other references (Task 2) for variable monetary rewards. Participants with lower levels of depressive symptoms showed a self-positivity bias, sacrificing rewards for the opportunity to engage in positive self-reference, whereas those with higher levels of depressive symptoms had no specific preference for either negative or positive self-reference (Task 1). However, all participants sacrificed monetary rewards for the opportunity for self-reference versus other reference, regardless of the symptom level or the primed valence (Task 2). Together, these findings suggest that depressive cognition could be characterised by the lack of intrinsic motivation for positive self-reference, which is attributable to the biased valence selection, but not to self–other preferences.